FAKTOR PERILAKU YANG BERHUBUNGAN DENGAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI PUSKESMAS KAHURIPAN KOTA TASIKMALAYA - Rahmani, Tharisa; Novianti, Siti; Yogaswara, Dadan (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2024)
Dengue fever stil a major health problem around the world. Tasikmalaya city as a endemic area . The sample for this study was 172 samples. The data collection is done by purposeful sampling technique. The data collection was done by questionnaire interview and observation. The results of the two-variable statistical test by chi-square analysis at 95% confidence showed that there was a relationship between the habit of hanging clothes (p=0.031), emptying the water bottle once a week (p = 0.016), the presence of reticular fibers (p = 0.001) increases the risk of dengue. There was no association between use of mosquito repellent (p=0.211) with dengue incidence. Communities should take dengue prevention measures such as emptying tanks at least once a week, shielding indoor ventilation, and not hanging clothes indoors to reduce dengue transmission.